Soft Simply Compact Spaces - Noori, S.; Yousif, Y. Y. (Iraqi Journal of Science, 2020)
The aim of this research is to use the class of soft simply open set to define new types of separation axioms in soft topological spaces. We also introduce and study the concept of soft simply compactness.